Postgraduate Certificate in Education (PGCE) Students’ Experience of Mentoring - du Plessis, Andre; Ismail, Bedroen (Revija za elementarno izobraževanje, 2022)
The school practicum is an essential component of pre-service student teachers’ training in the PGCE qualification, affording opportunities to develop mentees’ own identities. Along with a range of competences. This study explores how student teachers at Nelson Mandela University perceived their School-Based Learning (SBL) mentoring experience about the roles that mentors should fulfil based on an adapted seven-factor framework (Hudson, 2004, 2009) by adopting a post-positivist paradigm. The findings showed that both groups of participants who would like to return to the same mentor again or those who wish not to do so indicated that these seven factors played a crucial role in their decision-making.
Keywords: ICT modelling, ICT pedagogical knowledge, mentor, mentoring, model, personal attributes, pedagogical knowledge, system requirements